2022
DOI: 10.21203/rs.3.rs-1249472/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of General and Specific Combining Ability for Doubled Haploid Lines in Sweet Pepper (Capsicum Annuum L.)

Abstract: Hybrid cultivars are commercially and economically important; hence, too much effort needed to improve the quality and quantity of hybrids. In this research project, general (GCA) and specific (SCA) combining ability of 32 doubled haploid (DH) lines of sweet pepper produced via microspore embryogenesis were evaluated. The DH lines were crossed with the top cross parent as the tester to evaluate general combining ability (GCA). Traits including morphological and yield-related characteristics to assess the gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…On the other hand, the ability of improving fruit wall thickness through the current breeding program was moderate. That's maybe due to the selection of the prenatal genotypes was depending on the characters of yield, earliness, and fruit characters (Rathva et al,;Bayati et al, 2022). In accordance with the current investigation (Thilak et al, 2019) reported that the parents were found to be the best general combiner.…”
Section: )supporting
confidence: 82%
“…On the other hand, the ability of improving fruit wall thickness through the current breeding program was moderate. That's maybe due to the selection of the prenatal genotypes was depending on the characters of yield, earliness, and fruit characters (Rathva et al,;Bayati et al, 2022). In accordance with the current investigation (Thilak et al, 2019) reported that the parents were found to be the best general combiner.…”
Section: )supporting
confidence: 82%